2022
DOI: 10.3767/persoonia.2022.49.04
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, taxonomy, and character evolution inEntolomasubgenusNolanea

Abstract: Nolanea is a well-known and long-established subgenus of the genus Entoloma traditionally defined mainly by the mycenoid basidiocarps of the included species. Until now, revisions of this subgenus including molecular data exist only on a regional scale. In this study, the phylogeny of species of Nolanea is analysed based on multi-gene DNA sequences including data of specimens from all continents. New primers are designed for the mitochondrial small subunit and RPB2. The performance of the DNA loci in reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Based on these data, Cyanula has been raised to the subgenus level [ 26 ]. Recent studies [ 37 , 38 ] have shown that a clade of species around Entoloma ameides (sect. Ameides (Largent) Reschke et al) previously classified under the subgenus Nolanea now is grouped with the subgenus Leptonia as a sister to the /Leptonia clade with high support.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, Cyanula has been raised to the subgenus level [ 26 ]. Recent studies [ 37 , 38 ] have shown that a clade of species around Entoloma ameides (sect. Ameides (Largent) Reschke et al) previously classified under the subgenus Nolanea now is grouped with the subgenus Leptonia as a sister to the /Leptonia clade with high support.…”
Section: Introductionmentioning
confidence: 99%
“…Claudopus (He et al 2019) and species of subg. Nolanea (Reschke et al 2022b). Further, they have been used together for the species delimitation in subg.…”
Section: Discussionmentioning
confidence: 99%
“…Minuta of subg. Nolanea (Reschke et al 2022a). Entoloma colchicum shares some morphological and phylogenetic affinities with E. altaicum O.V.…”
Section: Entoloma Colchicummentioning
confidence: 96%
“…nih. gov) databases, as well as from recent publications (Co-David et al 2009;Battistin et al 2014;Morozova et al 2014b;Raj et al 2014;Vila et al 2014Vila et al , 2021Kim et al 2015;Kokkonen 2015;Crous et al 2016;Raj and Manimohan 2016;He et al 2019;Karstedt et al 2020;Sammut 2021;Sleiman et al 2021;Xing et al 2021;Jayawardena et al 2022;Noordeloos et al 2022a, b;Reschke et al 2022a, b;Voto 2023). The multiple sequence alignment was conducted using MAFFT 7.11 (Katoh et al 2019) with the E-INS-i algorithm.…”
Section: Dna Study and Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation